Clinical Profile of Stroke Patients with Vertigo in Hasan Sadikin General Hospital Bandung Neurology Ward - Amany Khansa; Aih Cahyani; Lisda Amalia (Journal of Medicine and Health, 2019)
Vertigo often occurs from the ages of 18 to 79 years with a prevalence of 7.4%. Central vertigo is less common than peripheral vertigo, but it can worsen disability in stroke patients. This study aims to determine the profile of stroke patients with vertigo in Hasan Sadikin General Hospital Bandung Neurology Ward. This is a retrospective descriptive study, using medical record data from 2013 to 2017, and collected 173 medical record data. The results showed that most stroke patients with vertigo were women (59%), the most age group was 55-64 years (34.1%), the most common type of stroke was ischemic stroke (75.7%), the most disturbance regarding the vertebrobasilar system was (72.8%), the most patients got the first stroke was (52.6%), 60.7% of patients suffered from hypertension, 23.1% of patients suffered from hyperlipidemia 40 (23.1%), and 22% of patients suffered from diabetes mellitus type 2. This study concludes that stroke patients who experience vertigo are more common in women, and in the 55-64 year age group. The most common stroke is ischemic in the vertebrobasilar system. Most symptoms in stroke patients with vertigo are dizziness not affected by position, vomiting and nystagmus. Hypertension, hyperlipidemia and diabetes mellitus play an important role in the incidence of stroke in patients. Keywords: vertigo, risk factor, stroke, vertebrobasilar